Spc29p is a component of the Spc110p subcomplex and is essential for spindle pole body duplication - Elliott, Sarah; Knop, Michael; Schiebel, Elmar (Proceedings of the National Academy of Sciences of the United States of America, 1999)
In yeast, microtubules are organized by the spindle pole body (SPB). The SPB is a disk-like multilayered structure that is embedded in the nuclear envelope via its central plaque, whereas the outer and inner plaques are exposed to the cytoplasm and nucleoplasm, respectively. How the SPB assembles is poorly understood. We show that the inner/central plaque is composed of a stable SPB subcomplex, containing the γ-tubulin complex-binding protein Spc110p, calmodulin, Spc42p, and Spc29p. Spc29p acts as a linker between the central plaque component Spc42p and the inner plaque protein Spc110p. Evidence is provided that the calmodulin-binding site of Spc110p influences the binding of Spc29p to Spc110p. Spc42p also was identified as a component of a cytoplasmic SPB subcomplex containing Spc94p/Nud1p, Cnm67p, and Spc42p. Spc29p and Spc42p may be part of a critical interface of nucleoplasmic and cytoplasmic assembled SPB subcomplexes that form during SPB duplication. In agreement with this, overexpressed Spc29p was found to be a nuclear protein, whereas Spc42p is cytoplasmic. In addition, an essential function of SPC29 during SPB assembly is indicated by the SPB duplication defect of conditional lethal spc29(ts) cells and by the genetic interaction of SPC29 with CDC31 and KAR1, two genes that are involved in SPB duplication.